Preparation and Characterization of Polyacrylamide – Silver Nanocomposite - Ahmed, Samira (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The preparation of polyacrylamide (PAAM)/silver (Ag) nanocomposites, transmission electron microscopy (TEM), X-ray powder diffraction (XRD), and vibrational structure were studied in this work. TEM results showed that the Ag particles were in sphere shape with 12 nm and 13 nm diameter. The X-ray diffraction results showed that, silver nanoparticles are present in the prepared nanocomposites 10 nm and 11 nm. The vibrational modes were analyzed by FTIR spectroscopy.